The Influence of Occupational Safety for Iron Frame Installation Project Workers Using FMEA Approach in CV. Sinar Surya Abadi Sidoarjo - Adityawan, Helga; Rusdiyantoro, . (Tibuana, 2024)
CV. Sinar Surya Abadi is a company engaged in the installation of iron frames. The manufacture of these products cannot be separated from hazardous equipment such as grinders, plasters, and others. This causes the risk of accidents at work. Thus the application of Occupational Safety and Health (K3) is very important to implement. Based on these problems, a study was made regarding the influence of work safety for project workers including iron with the FMEA approach on CV. Sidoarjo Eternal Sunshine. Occupational Health and Safety is a situation that affects the health and safety of workers or other employees. Occupational accidents can be reduced by implementing occupational safety and health (K3). FMEA is a structured procedure to identify and prevent as many failure modes as possible. FMEA focuses on preventing defects, increasing safety, and increasing customer satisfaction. The advantage of this FMEA is that it can improve the quality of control of the implementation of K3 so that it can prevent work accidents. FMEA serves to determine the actions of prioritized risks. The use of FMEA is also used to find out what potential risks exist in a production process. And also used to analyze failures from human error or the machine used.